HEAVY METALS ACCUMULATION AND THEIR EFFECTS ON A FEW ENZYMES IN NOTOPTERUS NOTOPTERUS - CHAND, RAMESH; SHANKAR, J. S.; KUMAR, P.; VERMA, S. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
The accumulation of mercury and cadmium in kidney and brain and alterations in the activity of glutamic-oxalacetic transaminase (GOT) and glutamic pyruvic transamina e (GPT) in kidney and brain were observed after 24, 48, 72 and 96 hr at 1/5th, 1110th and 1 5th fractions of 96 hr LCso of the fish Notopterus notopterus. Mercury and cadmium accumulated maximum in kidney (3.02 - 0.41 and 6.33 - 0.32 ppm) after 96 hr at 115th fraction and minimum in | brain (0.54 - 0.40 and 206 - 0.42 ppm) after 24 hr at 1115th fraction, respectively. GOT and GPT activity was stimulated significantly insignificantly in both the tissue.